Two new species of fleas of the genus Kohlsia Traub, 1950 (Siphonaptera: Ceratophyllidae) from Mexico - Acosta, Roxana; Salceda-Sánchez, Beatriz; Ponce-Ulloa, Hugo E. (Zootaxa, 2009)
Two new species of the genus Kohlsia Traub, 1950 from Mexico are described and illustrated, K. zyanya and K. ahuacatlan. A key to the species of Kohlsia known to occur in Mexico is provided.